Specific phospholipids regulate the acquisition of Neuronal and astroglial identities in post-mitotic cells - Montaner, Aneley Natalia (2018)
Fil: Fil: Montaner, Aneley Natalia. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Biología Molecular y Celular de Rosario (IBR -CONICET); Argentina.